Wedge resection and segmentectomy in patients with stage I non-small cell lung carcinoma - Konstantinos Reveliotis; George Kalavrouziotis; Konstantinos Skevis; Andriani Charpidou; Rodoula Trigidou; Kostas Syrigos (Frontiers Media S.A., 2014)
The use of sublobar resections as definitive management in stage I non-small cell lung carcinoma is a controversial topic in the medical community. We intend to report the latest developments and trends in relative indications for each of the above-mentioned surgical approaches for the treatment of stage I non-small cell lung carcinoma as well as the results of studies regarding local recurrence, disease-free survival and five-year survival rates. We reviewed 45 prospective and retrospective studies conducted over the last 25 years listed in the Pubmed and Scopus electronic databases. Trials were identified through bibliographies and a manual search in journals. Authors, citations, objectives and results were extracted. No meta-analysis was performed. Validation of results was discussed. Segmentectomies are superior to wedge resections in terms of local recurrences and cancer-related mortality rates. Sublobar resections are superior to lobectomy in preserving the pulmonary parenchyma. High-risk patients should undergo segmentectomy, whereas lobectomies are superior to segmentectomies only for tumors >2 cm (T2bN0M0) in terms of disease-free and overall 5-year survival. In most studies no significant differences were found in tumors <2 cm. Disease-free surgical margins are crucial to prevent local recurrences. Systematic lymphadenectomy is mandatory regardless of the type of resection used. In sublobar resections with less thorough nodal dissections, adjuvant radiotherapy can be used. This approach is preferable in case of prior resection. In pure bronchoalveolar carcinoma, segmentectomy is recommended. Sublobar resections are associated with a shorter hospital stay. The selection of the type of resection in T1aN0M0 tumors should depend on characteristic of the patient and the tumor. Patient age, cardiopulmonary reserve and tumor size are the most important factors to be considered. However further prospective randomized trials are needed to investigate the efficacy of minimal resections in early lung cancer patients.